Grandma's hair is ankle length = El cabello de abuela le llega hasta los tobillos - Camacho-Church, Adriana (Piñata Books, Arte Público Press, 2023)
"In this bilingual picture book with English and Spanish on the same page, a young girl treasures her grandmother's ankle-length hair, as well as the love, security and wisdom of ages it represents"--